Research of the CNC Side Milling Method for ZC3 Worm Gear - Hu Yangjing; Huang Xiaotiao; Fang Chenggang; Zhang Hu (Jixie chuandong)
In order to improve the precision of CNC machining ZC3 worm gear,a side milling method for machining worm gear is proposed. Firstly,the mathematical model for milling ZC3 worm gear is established based on the principle of gear meshing. Secondly,the worm gear tooth surface points are solved by MATLAB.By using the least square fitting method,the relationship between worm gear surface curvature and cross-sectional data from the worm gear axially is obtained. Then,the NC tool paths are generated by solving the non-uniform division method for tooth surface. Finally,the simulation of the generated machining program is carried out by using the VERICUT,the correctness of the proposed method is verified by comparing with the original calculation tooth surface data. The experiment shows that the proposed method can improve the milling universality as well as the efficiency compared with the conventional method for worm gear CNC machining.